Consumer Acceptance Studies Against Meat Jerky Climbing Perch (Anabas testudineus) With the use of Tapioca Flour - Nurhayati '; Mery Sukmiwati; Ira N Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this study was to determine the level of consumer acceptance of creamed fish jerky etching with the addition of tapioca flour and tapioca flour to get the right amount in the processing of pulverized jerky climbing perch. Treatment applied is the use of starch 4 levels DB0 (without the addition of starch), DB1 (addition of 50 g of tapioca starch), DB2 (addition of tapioca flour 75g), DB3 (the addition of starch 100 g). The parameters tested in this study is the organoleptic value (color, texture, taste and aroma), the proximate analysis (moisture content, protein content, and ash content). The results showed that the treatment of the most preferred consumers namely the addition of 50 g of starch with a value of 90.00% (72 people) with a water content of 12.89%, 24.80% protein, and ash content of 1.89%.Keywords: Fillet of creamed fish, damselfish, tapioca flour